2016
DOI: 10.1038/bjc.2016.356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of walking on circadian rhythms and sleep quality of patients with lung cancer: a randomised controlled trial

Abstract: Background: Sleep disturbances and poor rest-activity rhythms, which can reduce the quality of life, are highly prevalent among patients with lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 36 publications
3
85
1
1
Order By: Relevance
“…Two studies showed a significant effect for exercise effect on improving subjective sleep quality but had no significant effect on objective sleep quality (Chen et al, 2016;Rogers et al, 2017). Two studies showed a significant effect for exercise effect on improving subjective sleep quality but had no significant effect on objective sleep quality (Chen et al, 2016;Rogers et al, 2017).…”
Section: Summary Of Outcomesmentioning
confidence: 97%
See 4 more Smart Citations
“…Two studies showed a significant effect for exercise effect on improving subjective sleep quality but had no significant effect on objective sleep quality (Chen et al, 2016;Rogers et al, 2017). Two studies showed a significant effect for exercise effect on improving subjective sleep quality but had no significant effect on objective sleep quality (Chen et al, 2016;Rogers et al, 2017).…”
Section: Summary Of Outcomesmentioning
confidence: 97%
“…Of the 1,833 cancer patients, 1,324 were women, and 509 were men, (study sample sizes ranged from 19 to 277; Over half of the studies were performed in America (n = 13; Brown et al, 2018;Cheville et al, 2013;Coleman et al, 2012;Hacker et al, 2011;Ligibel et al, 2016;Mock et al, 1997;Payne et al, 2008;Rogers et al, 2017Rogers et al, , 2015Rogers et al, , 2013Rogers et al, , 2009Sprod et al, 2010;Wenzel et al, 2013), three were performed in Taiwan (Chen et al, 2016;Tang et al, 2010;Wang et al, 2011), two were investigated in Canada (Adams et al, 2018;Courneya et al, 2012), and four trials each were conducted in the UK (Donnelly et al, 2011), Netherlands (Kampshoff et al, 2015), Germany (Schmidt et al, 2015) and Iran (Shobeiri, Masoumi, Nikravesh, Heidari Moghadam, & Karami, 2016). Of the 1,833 cancer patients, 1,324 were women, and 509 were men, (study sample sizes ranged from 19 to 277; Over half of the studies were performed in America (n = 13; Brown et al, 2018;Cheville et al, 2013;Coleman et al, 2012;Hacker et al, 2011;Ligibel et al, 2016;Mock et al, 1997;Payne et al, 2008;Rogers et al, 2017Rogers et al, , 2015Rogers et al, , 2013Rogers et al, , 2009Sprod et al, 2010;Wenzel et al, 2013), three were performed in Taiwan (Chen et al, 2016;Tang et al, 2010;…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations